Genetic variation and adaptation to flooding in plants - Davy, A.; Noble, S.; Oliver, Richard (1990)
We review the evidence for genetic variation that can be associated with the evolution of adaptations to flooding: variation related to flooding at the level of molecular mechanism; comparisons of the patterns of variation in flooding-tolerant and non-tolerant species; within-species variation associated with genetically differentiated populations that experience different degrees of flooding. Many of the structural and physiological characteristics that enable certain higher plants to tolerate or avoid the effects of flooding are understood. Yet we know little of the genetic basis for these features and less of its variation. Few studies of adaptations to flooding have attempted to measure plant fitness and demonstrate selection or other evolutionary forces. We analyse a case study of Salicornia, which exists as locally differentiated populations in different tidal flooding regimes, from the lowest to the highest parts of salt marshes. Genetic differentiation can be demonstrated by significant selection coefficients against alien types in reciprocal transplant experiments. We have investigated the genetic variation within and between these populations using restriction fragment length polymorphism (RFLP) studies of the ribosomal DNA (rDNA). Two rDNA repeat unit types were found, only one of which occurs in any individual plant. Only the 12-kilobase (kb) fragment was found in populations that experience the most flooding, whereas plants on the highest parts of the marsh had only the 10.5-kb fragment. Typical lower and upper marsh populations were mixed in their fragment compositions, but lower marsh areas supported a higher frequency of the 12-kb fragment than upper marsh and depressions supported a higher frequency of the 12-kb fragment than raised interfluve areas. The use of such DNA variation, which is itself unselected, as a marker for selected genetic variation shows considerable promise for the future.